Respiratory Distress in Postanesthesia Care Unit: First Presentation of Coronavirus Disease 2019 in a 17-Year-Old Girl: A Case Report - Rahmanzade, Ramin (A A Pract, 2020)
A 17-year-old healthy girl underwent an uneventful esthetic septorhinoplasty. She was easily extubated and transferred to the postanesthesia care unit (PACU) with oxygen saturation (Spo(2)) of 96%. About 30 minutes after arrival in the PACU, she developed dyspnea with Spo(2) of 84% and promptly received oxygen with bilevel positive airway pressure in conjunction with low-dose corticosteroid. The subsequent chest computed tomography (CT) revealed bilateral patchy infiltrates similar to the radiologic findings of Coronavirus Disease 2019 (COVID-19). Finally, a reverse transcriptase polymerase chain reaction (RT-PCR) of a pharyngeal specimen confirmed the diagnosis of COVID-19.